2007
DOI: 10.1016/j.rmed.2007.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Airway involvement and obstruction from granulomas in African–American patients with sarcoidosis

Abstract: Sarcoidosis is a global disorder whose breadth of organ involvement can often be underappreciated. Head and neck manifestations include involvement of the skin, salivary glands, sinonasal cavity, and larynx. Of cases of upper airway sarcoidosis, laryngeal sarcoidosis and airway compromise portend a greater risk of fatal outcomes. People representing all racial groups have been diagnosed with sarcoidosis. Although many studies have evaluated incidence and manifestations of sarcoidosis in multiple ethnicities, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
(25 reference statements)
0
21
0
Order By: Relevance
“…The frequency of this localisation is conWrmed by a majority of studies on laryngeal sarcoidosis and case reports [27][28][29][30][31][32][33]. A diVerence in localisation was seen in the series of six African-American patients with laryngeal sarcoidosis, in which only two patients had limited supraglottic involvement and avoided tracheotomy, whilst four had extensive sarcoid granulomas involving two or three sections of the larynx and required surgical management due to upper airway obstruction [34].…”
Section: Extrathoracic Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of this localisation is conWrmed by a majority of studies on laryngeal sarcoidosis and case reports [27][28][29][30][31][32][33]. A diVerence in localisation was seen in the series of six African-American patients with laryngeal sarcoidosis, in which only two patients had limited supraglottic involvement and avoided tracheotomy, whilst four had extensive sarcoid granulomas involving two or three sections of the larynx and required surgical management due to upper airway obstruction [34].…”
Section: Extrathoracic Manifestationsmentioning
confidence: 99%
“…The diVerential diagnosis of laryngeal sarcoidosis includes epiglottitis, granulomatous laryngitis of another cause, including tuberculosis, histoplasmosis, blastomycosis, coccidioidomycosis, syphilis and actinomycosis, malignant neoplasm, cartilaginous tumours and rare diseases of the larynx such as Wegener's granulomatosis and amyloidosis [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Diverential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, involvement of nearly every part of the mucosa of the respiratory tract from the nasal cavity to the peripheral bronchioles has been described [9]. Localized, symptomatic laryngeal involvement is relatively rare [10]. A 31-year review at Mayo clinic identified 220/2319 (9%) patients with head and neck manifestations suffering from sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Localized laryngeal disease is treated with resection using CO 2 laser with local steroids or mitomycin-C. Open surgical excision and external radiation therapy may be also used. 33 Amyloidosis is usually localized in the head and neck area, treatment with surgical excision is usually successful for symptomatic cases. In the larynx, a conservative resection using microlaryngeal surgical approach is recommended with preservation of the surrounding tissue.…”
Section: Chart 2 Chartmentioning
confidence: 99%